Implementasi Laporan Keuangan Digital melalui Akuntansi UKM di Resto Olin’s Café Bekasi - Dyah Permatasari, Maulina; Yahya, Adibah; Bukhori Muslim, Ahmad; Yulianik, Yulianik; Aulia Masduki, Farah (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia have become the biggest contributor to economic growth. The success of small and medium businesses is inseparable from digital developments. In increasing financial managerial capacity in terms of financial reporting, one of the methods used is to prepare financial reports with the help of the SME Accounting application. Community service implementation partners are SMEs engaged in buying and selling groceries. In order to improve financial literacy of partners, the methods used are in the form of lectures, discussions, mentoring and practice. In implementing the SME Accounting application, partners are assisted in creating accounts and inputting transactions. The purpose of this activity is to facilitate partners in preparing financial reports through the implementation of the SME Accounting application. The results of the activity show that partners are assisted by this activity, and hope that this activity can continue